Diseño de catálogo interactivo de las principales piezas arqueológicas existentes en la casa de la cultura "Benjamín Carrión" Núcleo de Cotopaxi. - Ayala Trujillo, Gabriela Maritza (2018)
The present research project was carried out in order to disseminate the main archaeological pieces of the different cultures exhibited in the Molinos Monserrat museum of the Ecuadorian Culture House "Benjamín Carrión" Núcleo de Cotopaxi, through an interactive digital catalog , in order to make the information known in an agile and timely manner, for which the 360 ° photography technique was used, since it is considered as a technological trend at present, with the sole purpose of contributing to cultural enrichment of the population. The interactive digital catalog strategy generates an indirect marketing bonus for the Culture Center of Cotopaxi, since in several Ecuadorian museums so far have similar works that allow to inform and interact directly with users. , considering that multimedia is one of the most versatile resources to transmit information. For the research and development of the interactive digital catalog proposal, the following methodologies were adopted: the Transparent Box by Christopher Jones, the method that had a clear defense set in terms of objectives, variables and criteria, which were analyzed by generating a user experience or user experience of Jesse James Garett. The same time that was adapted to the requirements, which focuses directly with the proposal, to solve and meet the specific needs of our users, achieving greater satisfaction and better Possible usage experience with minimal effort.